Gerakan Politik Islam Substantif dan Formalis menurut Filsafat Hikmah Muta’aliyah - Nano warno (Emanasi : Jurnal Ilmu Keislaman dan Sosial, 2020)
This article aim to analyze the phenomenon of the contemporary Indonesian Islamic political movement that is framed into two formalist and substantive camps from the perspective of the philosophy of Hikmah Muta'aliyah. The philosophy of HIkmah Mutaaliyah which was developed by Mulla Sadra, a 20th century philosopher who has a rich capital that can inspire the emergence of discourses that are relevant to various contemporary issues including the phenomenon of contemporary Indonesian political movements. The method used is transcendental hermenetics which is extracted from its existential principles such as existential fundamentals (ashalat wujud) and substantial transformation (harakah jawhariayh) and their ethical principles. Humans will experience a transformation depending on the knowledge gained and also practical actions which then shape ideology, including seeing Islam.